School-Based Disaster Psychoeducation to Improve Student Preparedness in Hydrometeorological Disasters: Psikoedukasi Kebencanaan Berbasis Sekolah untuk Meningkatkan Kesiapsiagaan Siswa Menghadapi Bencana Hidrometeorologi - Sari, Reza Lidia; Herdiana, Ike; Lakoro, Rahmatsyam (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Indonesia's geographical location makes it a potential country to experience natural disasters. As a vulnerable group, children need to receive information on preparedness for natural disasters. Therefore, the community service team designed and implemented the "PETACANA” as a disaster psychoeducation program at the school level. PETACANA aims to increase students' awareness of the risks of natural disasters and their impacts, as well as increase students' knowledge about mitigation and preparedness in facing them. The PETACANA was implemented at SDN Kalipang 01 Blitar on June 17th, 2023 involving 60 students from grades IV and V in elementary school. The program was carried out through lecture, group discussions, and creating disaster education posters. Wilcoxon Signed Rank Test showed that the PETACANA Program was significantly increased students' knowledge regarding risks, impacts, mitigation, and preparedness in facing natural disasters. Thus, schools need to implement disaster education programs to increase students' preparedness in facing disasters.